Creation as Text: The Graphological Trope in Said Nursi's Risāle-i nūr. Issue 3 (October 2019) - Turner, Colin
Abstract : Reading the act of creation as written or spoken narrative seems to have gained currency across the faith traditions from very early on. The Muslim tradition is no exception. As the 'pen and ink' verse in the Qur'an shows, the notion of creation as an assemblage of divine words is as old as Islam itself. It was not until the advent of Muslim mysticism, however, that writers began to build on the image's revelatory foundations. The present study is an introductory analysis of extended metaphor in the work of the Ottoman theologian Bediüzzaman Said Nursi, with particular reference to the use of the 'graphological trope' in his six-thousand-page exegesis of the Qur'an known as the Risale-i Nur ('The Epistles of Light'). The aim is to draw attention to Nursi's use of a particular literary conceit that is deserving of further study. Of the few works on Nursi and his teachings that stand up to serious academic scrutiny, nothing of substance has been written about the language of the Risale-i Nur . It is hoped that this exploratory article will spur other scholars on to a more extensive survey and analysis of imagery in Nursi's oeuvre .